Monetary Policy, Fiscal Policy and Capital Structure - ZIA UR REHMAN; ASAD KHAN; SHER ALI KHAN; SHAH RAZA KHAN (Journal of Business & Tourism, 2021)
Instruments of monetary and fiscal policy are beyond the control of the management but they do influence the short-term as well as long-term decision making of the firm. Empirical studies with respect to their effect on financing decisions of the firm are somewhat under researched particularly in the context of developing countries. The aim of the study was to analyse the effect of these instruments on the financing decisions of the non-financial firms listed on PSX for the period 2008-2015. Fixed effect model was used to analyse the effect of instruments of monetary policy and fiscal policy on the financing decisions of firms. Based on sample of 338 firms, the findings of the study revealed that instruments of monetary policy and fiscal policy do influence the financing decisions of the firm. M2, tax revenue and government debt has a significant effect on the debt ratio of listed firms whereas real interest rate is insignificantly related. Moreover, the relationship between real interest rate, M2 and tax revenue and debt ratio is negative whereas in case of government debt it is positive.